The Discourse of Disability in the Qur'an: A Methodological Application of Tafsīr Maqāşidī Waşfī 'Āsyūr Abū Zaid - Nurul; Muhammad Ulinnuha; Muhammad Ziyad Ulhaq (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2023)
This paper aims to elaborate on transforming the meaning of the term disabled contained in the Qur'an. The existence of disabled vocabulary that is commonly understood is often interpreted in terms of locus and does not include nonphysical aspects. If it is elaborated further, one will find that the Qur'an discusses not only the physical aspects of people with disabilities but also nonphysical aspects, which are referred to as